2017
DOI: 10.1021/acs.macromol.7b01096
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Multicomponent Polymerizations of Alkynes, Sulfonyl Azides, and Iminophosphorane toward Heteroatom-Rich Multifunctional Poly(phosphorus amidine)s

Abstract: Multicomponent polymerization (MCP) is a fascinating synthetic method for the construction of polymers with diverse structures and multifunctionalities. As a rapidly developing field, MCP begins to show great impact in polymer chemistry and polymer materials, which attract scientists' attention by their high convenience and efficiency, great structure diversity, high atom economy, and environmental benefit. In this work, a facile one-pot three-component polymerization of diynes, disulfonyl azides, and iminopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 61 publications
0
52
0
Order By: Relevance
“…Apparently, the UV emission of BSA solutions with E m ≈348 nm predominantly arises from the Trp residues, the photophysical properties of which have been well‐documented by previous pioneers . Their visible emission, however, should principally stem from the aggregation of nonaromatic subgroups and the peptide backbone, on account of their highly similar emission behaviors to those of nonconventional luminogens . In extremely dilute solutions, on the one hand, Trp residues are inefficient in terms of emission owing to the low concentration and long λ ex , and on the other hand, it is difficult to excite and induce emission in the BSA backbone owing to its insufficient conjugation and active molecular motions, thus resulting in the nonemissive feature of dilute solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the UV emission of BSA solutions with E m ≈348 nm predominantly arises from the Trp residues, the photophysical properties of which have been well‐documented by previous pioneers . Their visible emission, however, should principally stem from the aggregation of nonaromatic subgroups and the peptide backbone, on account of their highly similar emission behaviors to those of nonconventional luminogens . In extremely dilute solutions, on the one hand, Trp residues are inefficient in terms of emission owing to the low concentration and long λ ex , and on the other hand, it is difficult to excite and induce emission in the BSA backbone owing to its insufficient conjugation and active molecular motions, thus resulting in the nonemissive feature of dilute solutions.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] Their visible emission, however,s hould principally stem from the aggregation of nonaromatic subgroups and the peptide backbone,o n account of their highly similar emission behaviors to those of nonconventional luminogens. [19,[30][31][32][33][34][35] In extremely dilute solutions,o nt he one hand, Tr p residues are inefficient in terms of emission owing to the low concentration and long l ex ,a nd on the other hand, it is difficult to excite and induce emission in the BSA backbone owing to its insufficient conjugation and active molecular motions,thus resulting in the nonemissive feature of dilute solutions.W hent he concentration increases,B SA chains become entangled and aggregated, which allows the clustering of NH 2 ,C =O, OH, and other subunits with p and nelectrons,thus yielding 3D through-space electronic communication. Specifically,electronic orbital overlap among lone pairs and p electrons, dipole-dipole interactions,and n-p*interactions,bring about extended electronic delocalization along with simultaneously rigidified conformations.I np articular,s trong inter-a nd intramolecular hydrogen bonds not only stabilize the molecular conformations,b ut also facilitate contact between the subgroups,w hich is beneficial for light emission.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 For example, Chang et al have reported a series of facile and efficient Cu-catalyzed multicomponent couplings of sulfonyl azides, alkynes and nucleophiles. 4447 Attracted by their unique advantages, some of them have been developed into efficient polymerization tools to synthesize high-molecular-weight functional polymers, such as poly(N-sulfonylamidine)s, 40,48,49 poly(N-sulfonylimidate)s, 48,50 and poly(phosphorus amidine)s. 51 Recently, a copper-catalyzed three-component reaction of terminal alkynes, sulfonyl azides and carbodiimides (Scheme 1A) have caught our attention. 52 This MCR can generate 2,4-diiminoazetidine derivatives, a multisubstituted nitrogen-bearing four-membered heterocyclic system, under mild conditions in excellent yields from readily available substrates.…”
Section: Introductionmentioning
confidence: 99%